Monitoring the development of HIFU‐induced cavitation activity - Farny, C; Holt, G; Roy, R (AIP Publishing, 2006)
One of the limitations of HIFU treatment for tissue necrosis is the difficulty in achieving a predictable lesion shape and size in a short amount of time. Simply increasing the HIFU intensity cannot solve this problem, as it leads to the formation of a so‐called “tadpole”—shaped lesion. Bubble shielding of the incident HIFU is one of the mechanisms implicated in the development of these deformed lesions; at super‐nucleation pressures inertial cavitation will commence and the scattering from bubbles in the path of the ultrasound propagation will reflect the HIFU energy back towards the transducer. In the past we have employed a single focused, passive broadband transducer (PCD) to detect inertial cavitation activity at the HIFU focus in agar‐graphite tissue phantoms. At sufficiently‐high pressures, the inertial cavitation signal decreases over time, giving rise to the notion that bubble shielding is at fault for the signal decrease. Here we present evidence that bubble shielding is not the only mechanism behind such a change in the signal. As the medium heats up, inertial bubble collapses are cushioned by vapor and a decrease in signal amplitude from cavitation is to be expected. In order to evaluate the relative effects of the temperature rise and bubble shielding on bubble activity, we positioned a second PCD to sense noise emissions from various locations in the pre‐focal region along the HIFU axis. A decline in the cavitation signal from the focus was accompanied by an increase in pre‐focal bubble activity. The timescale for these changes suggests that both temperature and bubble shielding effects play a role in the bubble activity at the focus, and may provide information on how best to monitor the cavitation signal and ultimately provide feedback information necessary to control the HIFU insonation parameters to avoid bubble shielding.